1992
DOI: 10.1007/bf02899905
|View full text |Cite
|
Sign up to set email alerts
|

Effect of crude bacterial lipids on the course ofListeria infection in mice

Abstract: Crude lipids from 37 strains belonging to 32 bacterial species were isolated. By injecting mice with lipids 5 d prior to challenge with a virulent strain of Listeria monocytogenes, immunostimulatory activity in 19 preparations was found. In general, lipids of Gram-negative bacteria appeared to be more effective. As to bacilli, an extraordinary activity was found in the lipids of Bacillus firmus. Lipids of various species of the genus Listeria were found to be active in approximately one-half of cases. Among ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…Our studies of immuno-modulating properties of microorganisms revealed that the G+ bacterium B. firmus has pronounced immuno-stimulatory properties and, live or dead, it is harmless to mice in vivo; in addition, even high doses of inactivated bacterium do not suppress the viability of cells in culture [4][5][6][7][8]. Excellent adjuvant properties of this bacterium, which were proved in immunization of mice with ovalbumin via the respiratory tract [22] were confirmed in the intratracheal immunization of mice against type B influenza virus.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Our studies of immuno-modulating properties of microorganisms revealed that the G+ bacterium B. firmus has pronounced immuno-stimulatory properties and, live or dead, it is harmless to mice in vivo; in addition, even high doses of inactivated bacterium do not suppress the viability of cells in culture [4][5][6][7][8]. Excellent adjuvant properties of this bacterium, which were proved in immunization of mice with ovalbumin via the respiratory tract [22] were confirmed in the intratracheal immunization of mice against type B influenza virus.…”
Section: Discussionmentioning
confidence: 98%
“…An extensive screening performed several years ago [4] showed that Bacillus firmus (BF), a non-pathogenic and non-toxigenic G+ bacterium of the environment, exceeds other G+ bacteria in its ability to stimulate anti-infectious immunity during experimental listeria infection in mice. Later, we showed stimulatory effects of BF on macrophage and lymphocyte activation in mice [5][6][7][8] and on anti-tumor activity in rats [9].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, activation of NK cells might be an essential step in therapy, especially in cases of NK cell deficiency such as malignant diseases [40]. B. firmus, a nonpathogenic bacterium of the environment, possessed different immunomodulatory properties in vitro and in vivo [24][25][26][27][28][29], including immunostimulating effects on human [27] and murine B lymphocytes [25] and macrophages [28]. Furthermore, a study from Lomakova and colleagues showed the ability of inactivated B. firmus to activate murine peritoneal cells and enhanced production of several important immunomodulatory cytokines in vitro [41].…”
Section: Discussionmentioning
confidence: 99%
“…Bacillus (B.) firmus, a non-pathogenic and non-toxigenic gram-positive bacterium of the environment, possessed different immunomodulatory properties in vitro and in vivo [24][25][26][27][28][29]. B. firmus showed immunostimulating effects on human [27] and murine B lymphocytes [25] and macrophages [28].…”
Section: Introductionmentioning
confidence: 99%
“…The use of CT in humans is excluded because of its high toxicity; a number of LT mutants have been prepared that retain their adjuvant activity; these mutants were likewise tested on the mouse model and should not cause any serious side effect in humans [19]. Current studies aim at finding a suitable and safe mucosal adjuvant applicable in humans that could increase both mucosal and systemic immune response [20][21][22][23]. Such adjuvant is needed especially for immunization with subunit vaccines.…”
Section: Discussionmentioning
confidence: 99%